Assessing remote physiological signals acquisition experiments - Barros, Carla (2015)
A great number cif remote laboratories has been implemented in the engineering field. Nevertheless, there are few approaching the bioengineering area. The present paper will describe not only an innovative remote laboratory developed for biomedical engineering education, but also its assessment based on the target public's feedback. The remote laboratory developed by the research team intends to provide the physiological signals remote acquisition from human body, supported by theory to a greater understanding of learned concepts. This tool is geared towards the undergraduate biomedical engineering students. Therefore, a sample of twelve students took part in a limited study conducted to quantitatively and qualitatively assess the remote laboratory. The study was undertaken using two questionnaires, one distributed before and other after the performance of a remote experiment. Moreover, the information about the learning style/method, employed by each student, was collected in order to devise strategies for future applications development and to make the remote laboratory suitable for the target public.